Pengembangan Prototype Kurikulum Adiwiyata Berbasis E-Learning di Sekolah Menengah Atas Negeri 4 Tangerang Selatan - Arvita Dewi Febrianti; Ulfhatun Widiastuti; Rastianta Rinandani; Daniel Mongan; Desi Rahmawati (Risenologi, 2021)
The older the earth, the more problems that occur on earth, one of which is global warming. We can fix all of that in various ways, one of which is through the Adiwiyata program. The learning process is realized through the school curriculum that leads to efforts to build the character and behavior of teachers and students who care about the environment. The use of e-learning is expected to improve the quality of learning and the independence of students, and the interaction between educators and students. So the researchers decided to conduct research on the Development of the Adiwiyata Curriculum Prototype Based on E-Learning at SMAN 4 South Tangerang. This research is a research and development (RnD) research. Sources of data in this study are primary data and secondary data. Data collection techniques used are observation, documentation, and interviews. The results of this study are a prototype of the Adiwiyata Curriculum based on E-Learning in the form of an android application. This application is called Go Green School which includes 4 programs, namely Care for Waste From Home, Reduce-Reuse-Recycle Online, Planting Trees From Home, and Changing Clothes and Thrifting Online, which can be used as guidelines in implementing Adiwiyata training programs at State Senior High Schools. 4 South Tangerang.